COMPETENCE OF PROFESSIONAL TEACHERS FACING 21st CENTURY LEARNING THROUGH 4C COLLABORATION, COMMUNICATION, CRITICAL THINKING, CREATIVITY) - Indriyani, Yuni; Siti Maryam Rohimah (Pasundan International of Community Services Journal (PICS-J), 2024)
This activity is carried out to improve the Competence of Professional Teachers in Facing 21st Century Learning Through 4C (Collaboration, Communication, Critical Thinking, Creativity). In this training, teachers will receive training in the preparation of lesson plans that can develop the 4Cs. Teachers who are trained are expected to improve their performance in achieving achievement and quality of learning continuously. The training uses an interactive, dialogical and participatory pattern with an andragogic learning approach, horizontal relationships between participants and trainers by identifying the needs, resources and obstacles faced by teachers in developing integrated learning plans in their respective schools. The output target is that teachers have optimal pedagogical competence in carrying out their roles and functions professionally so that learning is more interesting.